2022
DOI: 10.3389/fphot.2022.940902
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing supercontinuum spectro-temporal properties by leveraging machine learning towards multi-photon microscopy

Abstract: Multi-photon microscopy has played a significant role in biological imaging since it allows to observe living tissues with improved penetration depth and excellent sectioning effect. Multi-photon microscopy relies on multi-photon absorption, enabling the use of different imaging modalities that strongly depends on the properties of the sample structure, the selected fluorophore and the excitation laser. However, versatile and tunable laser excitation for multi-photon absorption is still a challenge, limited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…To that end, it is possible to use machine learning methods in order to have some additional control of the coherent dynamics. For example, genetic algorithms were used to prepare custom pulse-trains with an integrated pulse-splitter as to maximise the spectral density in defined wavelength ranges of the SC [ 236 , 237 ]. It was also shown that Gaussian-like peaks can be intentionally positioned in the spectrum of the generated SC, by changing the spectral phase of the incoming pulse with a genetic algorithm [ 238 ].…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…To that end, it is possible to use machine learning methods in order to have some additional control of the coherent dynamics. For example, genetic algorithms were used to prepare custom pulse-trains with an integrated pulse-splitter as to maximise the spectral density in defined wavelength ranges of the SC [ 236 , 237 ]. It was also shown that Gaussian-like peaks can be intentionally positioned in the spectrum of the generated SC, by changing the spectral phase of the incoming pulse with a genetic algorithm [ 238 ].…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…More recently, PCFs have transitioned from the confines of the laboratory to find utility in various fields such as optical communication, fiber light sources, fiber optic sensors, non-linear devices, and opto-fluidic devices [5][6][7]. Moreover, these fibers play a crucial role in the development of broad supercontinuum (SC) sources [8][9][10], which have found applications in a wide range of fields, including optical coherence tomography, optical metrology, and spectroscopy [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively applied in image recognition and classification [3,4], natural language processing [5], time-series prediction [6], cybersecurity [7], healthcare [8], autonomous vehicle control [9] and neuroscience research [10]. In the recent years, machine learning techniques have also been developed for different applications in optics [11][12][13], such as inverse design of photonic structures [14], and optical microscopy [15].…”
Section: Introduction -Machine Learningmentioning
confidence: 99%